2018
DOI: 10.3899/jrheum.170837
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Osteonecrosis in Systemic Lupus Erythematosus: A Systematic Review and Metaanalysis

Abstract: Objective.Nontraumatic osteonecrosis (ON) is a well-recognized complication causing disability and affecting quality of life in patients with systemic lupus erythematosus (SLE). The aim of this study was to identify the risk factors for ON, and to identify the minimal investigation(s) needed to optimally monitor the risk of ON in patients with SLE.Methods.A systematic review was conducted using MEDLINE and EMBASE. These databases were searched up to January 2016 using the Medical Subject Heading (MeSH) terms “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 53 publications
2
55
0
6
Order By: Relevance
“…CS-induced ON tends to be multifocal lesions at multiple joints, as illustrated by studies of patients with SLE who are on long-term CS therapy (2,18,19). Similarly, we found that five of 16 (31.3%) patients with knee joint ON had femoral head ON who were complaining of hip joint pain.…”
Section: Discussionsupporting
confidence: 61%
“…CS-induced ON tends to be multifocal lesions at multiple joints, as illustrated by studies of patients with SLE who are on long-term CS therapy (2,18,19). Similarly, we found that five of 16 (31.3%) patients with knee joint ON had femoral head ON who were complaining of hip joint pain.…”
Section: Discussionsupporting
confidence: 61%
“…The occurrence of osteonecrosis in patients with SLE could be affected by various factors. The long-term use of corticosteroid is certainly a strong risk factor of osteonecrosis, but neuropsychiatric manifestations of SLE, vasculitis, hypertension, serositis, and renal disease could also increase the risk of osteonecrosis [15]. In addition, it is estimated that more than half of the SLE patients who have osteonecrosis will progress and finally require surgical intervention [16].…”
Section: Discussionmentioning
confidence: 99%
“…There is very low-to low-quality evidence for a small association of most risk factors with osteonecrosis. In patients with a high suspicion of osteonecrosis owing to clinical symptoms, it is unclear whether laboratory tests such as aPL could be used to evaluate the risk of osteonecrosis 57 . The panel agreed that the accuracy of different imaging modalities would be similar in the general population and in patients with SLE, that radiographs are less expensive than bone scan with SPECT or MRI, and some regions may not have access to the latter.…”
Section: Osteonecrosis Recommendationsmentioning
confidence: 99%